2006
DOI: 10.1523/jneurosci.0959-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Alzheimer Disease Family History and Apolipoprotein E ε4 on Mesial Temporal Lobe Activation

Abstract: First-degree family history of sporadic Alzheimer disease (AD) and the apolipoprotein E 4 (APOE4) are risk factors for developing AD. Although the role of APOE4 in AD pathogenesis has been well studied, family history remains a rarely studied and poorly understood risk factor. Both putatively cause early brain changes before symptomatic disease, but the relative contribution of each to brain function is unknown. We examined 68 middle-aged participants with a parent diagnosed with AD [family history (ϩFH)] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(159 citation statements)
references
References 82 publications
6
152
1
Order By: Relevance
“…Prior studies have reported fMRI alterations in cognitively normal (2,7,19,33,36,61,71) or mildly impaired (3,15) APOE*4+ individuals. However, there is considerable variability in both the direction and pattern of the differences.…”
Section: Altered Brain Activation In Apoe*4 Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported fMRI alterations in cognitively normal (2,7,19,33,36,61,71) or mildly impaired (3,15) APOE*4+ individuals. However, there is considerable variability in both the direction and pattern of the differences.…”
Section: Altered Brain Activation In Apoe*4 Carriersmentioning
confidence: 99%
“…Studies with fMRI have been less consistent; both increased (3,19,26,62,71), decreased (36,61) and unchanged (1) BOLD responses have been reported in APOE*4+ subjects and no clear anatomic region is reliably affected. Furthermore, recent fMRI studies suggest that a family history of dementia may modulate the effects APOE*4 on brain activation (33) or more robustly impact brain activation than APOE genotype (1).…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation is typically that reduced activation in this region corresponds to the memory deficits exhibited by these patients. However, this interpretation is complicated by a number of studies that have found increased MTL activation in MCI patients relative to healthy subjects [37,[40][41][42][43] as well as healthy older adults at genetic risk for AD versus those not at risk [44,45]. The interpretation of this increased activation, or 'hyperactivation', is that early in the progression of AD, there is a period of compensatory brain change, enabling patients to maintain function.…”
Section: Mtl Activation: Powers Pitfalls and Possibilitiesmentioning
confidence: 99%
“…For example, family history may interact with APOE status to influence activation [45]. Additionally, measuring the extent of activation as opposed to the magnitude of activation may yield different findings.…”
Section: Editorialmentioning
confidence: 99%
“…Neuroimaging studies of people at risk for developing AD report either reduced BOLD signal (Johnson et al, 2006b) related to AD risk factors or increased signal attributed to putative compensatory phenomena (Bookheimer et al, 2000). The fMRI BOLD signal itself is sensitive to changes in baseline cerebral blood flow (CBF) and cerebral metabolism of oxygenation that tightly accompany focal neuronal activity (Hoge et al, 1999;Ogawa et al, 1990).…”
Section: Introductionmentioning
confidence: 99%